2017
DOI: 10.13189/saj.2017.050302
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the Functional Movement Screen Score and Y-Balance Test Reach Distances

Abstract: Background: The Functional Movement Screen (FMS) is used to evaluate key movement patterns, functional symmetry, and identify individuals that are at elevated risk of injury. The purpose of this study was to assess whether dynamic postural control is a significant component of the composite FMS score by comparing it with Y-Balance Test (YBT) reach distances. Methods: Seventy-eight participants (including 40 males) performed the standardized FMS protocol followed by the YBT. The YBT reach distances were normali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In other studies conducted on university-trained athletes, a positive correlation was found between the FMS total scores and total LQYBT scores (18,31). In another study conducted on sedentary female and male individuals, a weak positive correlation was found between FMS and LQYBT total scores (15). Silva et al (28) stated that they found a positive relationship between FMS total score and CMJ in a similar study on soccer players.…”
Section: Discussionmentioning
confidence: 89%
“…In other studies conducted on university-trained athletes, a positive correlation was found between the FMS total scores and total LQYBT scores (18,31). In another study conducted on sedentary female and male individuals, a weak positive correlation was found between FMS and LQYBT total scores (15). Silva et al (28) stated that they found a positive relationship between FMS total score and CMJ in a similar study on soccer players.…”
Section: Discussionmentioning
confidence: 89%
“…It is required for locomotion skills such as walking and running, and therefore dynamic balance is a key element in preventing sports injuries [9]. However, many studies of the relationship of the FMS and dynamic balance have been carried out using mainly the Y-Balance test and the Star Excursion [10][11][12][13][14][15]. In most studies, the tests used were based on the subject's immobile position, in which the subject reaches out with a limb or tilts the whole body in a certain direction [16].…”
Section: Introductionmentioning
confidence: 99%
“…Functional training is designed to enhance dayto-day activities, recreational activities and/or sports activities. The object of this training is the neuromuscular system, where movements are trained (muscle groups and nervous system), not only muscles (Beckham & Harper, 2010). Functional workouts are effective in improving muscle strength, balance, mobility, and the quality of daily movements.…”
Section: Introductionmentioning
confidence: 99%